2017
DOI: 10.22159/ajpcr.2017.v10i8.18558
|View full text |Cite
|
Sign up to set email alerts
|

Assess the Prevalence of Hypertension and Knowledge Regarding the Prevention of Stroke

Abstract: Objective: Hypertension is the most crucial and common health problem in developed and undeveloped countries. Although hypertension is a treatable condition, without treatment, it leads to serious and life-threatening complications such as heart, kidney, and brain disorders. Prevention plays a major role in controlling the disease, which can be achieved by increasing the knowledge through awareness of the public and changing their attitude and practice. The study was aimed to assess the prevalence of hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…with hypertension [21]. Contradictory to our study most of the subjects 47 (78.3%) had inadequate knowledge, 13 (21.7%) had moderate knowledge, and none of them had adequate knowledge regarding prevention of stroke.…”
Section: Discussionsupporting
confidence: 44%
“…with hypertension [21]. Contradictory to our study most of the subjects 47 (78.3%) had inadequate knowledge, 13 (21.7%) had moderate knowledge, and none of them had adequate knowledge regarding prevention of stroke.…”
Section: Discussionsupporting
confidence: 44%
“…We found poor knowledge of risk factors and warning signs, and inadequate practice with respect to stroke. Similarly, another study in Kottayam reported that of 60 selected patients, 47 patients had inadequate knowledge, 13 had moderate knowledge, and none had sufficient knowledge regarding stroke prevention [12].…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] As the study conducted in India among people with hypertension on knowledge of stroke prevention revealed that 70% of hypertensive patients had inadequate knowledge, 30% had moderate knowledge regarding. 11 Another study conducted in Nigeria among hypertensive patients on knowledge and practices of stroke prevention showed that 90.8% of the study participants had good knowledge of stroke prevention modalities. 12 According to the World Health Organization report (2017) in Ethiopia, stroke was the second leading cause of death (6.23%) and it was a massive financial burden not only for patients but also for society as a whole.…”
Section: Introductionmentioning
confidence: 95%